Association of candidate genetic variants and circulating levels of ApoE/ApoJ with common neuroimaging features of cerebral amyloid angiopathy - Bonaterra-Pastra, Anna; Benítez, Sònia; Pancorbo, Olalla; Rodríguez-Luna, David; Vert, Carla; Rovira, Alex; Freijo, M. Mar; Tur, Silvia; Martínez-Zabaleta, Maite; Cardona Portela, Pere; Vera, Rocío; Lebrato-Hernández, Lucia; et al. (Frontiers in Aging Neuroscience, 2023)
Introduction Cerebral amyloid angiopathy (CAA) is characterized by the accumulation of amyloid-β (Aβ) in brain vessels and is a main cause of lobar intracerebral hemorrhage (ICH) in the elderly. CAA is associated with magnetic resonance imaging (MRI) markers of small vessel disease (SVD). Since Aβ is also accumulated in Alzheimer’s disease (AD) in the brain parenchyma, we aimed to study if several single nucleotide polymorphisms (SNPs) previously associated with AD were also associated with CAA pathology. Furthermore, we also studied the influence of APOE and CLU genetic variants in apolipoprotein E (ApoE) and clusterin/apolipoprotein J (ApoJ) circulating levels and their distribution among lipoproteins. Methods The study was carried out in a multicentric cohort of 126 patients with lobar ICH and clinical suspicion of CAA. Results We observed several SNPs associated with CAA neuroimaging MRI markers [cortical superficial siderosis (cSS), enlarged perivascular spaces in the centrum semiovale (CSO-EPVS), lobar cerebral microbleeds (CMB), white matter hyperintensities (WMH), corticosubcortical atrophy and CAA-SVD burden score]. Concretely, ABCA7 (rs3764650), CLU (rs9331896 and rs933188), EPHA1 (rs11767557), and TREML2 (rs3747742) were significantly associated with a CAA-SVD burden score. Regarding circulating levels of apolipoproteins, protective AD SNPs of CLU [rs11136000 (T) and rs9331896 (C)] were significantly associated with higher HDL ApoJ content in the lobar ICH cohort. APOEε2 carriers presented higher plasma and LDL-associated ApoE levels whereas APOEε4 carriers presented lower plasma ApoE levels. Additionally, we observed that lower circulating ApoJ and ApoE levels were significantly associated with CAA-related MRI markers. More specifically, lower LDL-associated ApoJ and plasma and HDL-associated ApoE levels were significantly associated with CSO-EPVS, lower ApoJ content in HDL with brain atrophy and lower ApoE content in LDL with the extent of cSS. Discussion This study reinforces the relevance of lipid metabolism in CAA and cerebrovascular functionality. We propose that ApoJ and ApoE distribution among lipoproteins may be associated with pathological features related to CAA with higher ApoE and ApoJ levels in HDL possibly enhancing atheroprotective, antioxidative, and anti-inflammatory responses in cerebral β-amyloidosis.